Remifentanil for endotracheal intubation in premature infants: A randomized controlled trial - Zohreh Badiee; Mazyar Vakiliamini; Majid Mohammadizadeh (Wolters Kluwer Medknow Publications, 2013)
Objective: Endotracheal intubation is a common procedure in neonatal care. The objective of this study was to determine whether the premedication with remifentanil before intubation has analgesic effects in newborn infants. Methods: A total of 40 premature infants who needed endotracheal intubation for intubation-surfactant-extubation method were randomly assigned in two groups of an equal number at two university hospitals. The control group was given 10 μg/kg atropine IV infusions in 1 min and then 2 ml normal saline. In the case group, the atropine was given with the same method and then remifentanil was administered 2 μg/kg IV infusions in 2 min. Findings: For remifentanil and control groups, the mean birth weight were 1761 ± 64 and 1447 ± 63 grams (P = 0.29), and the mean gestational ages were 31.69 ± 3.5 and 30.56 ± 2.8 weeks (P = 0.28), respectively. Using premature infant pain profile score, infants who received remifentanil felt significantly less pain than the control group (15.1 ± 1.6 vs. 7.5 ± 1.4; P < 0.001). There were no significant differences in the duration of endotracheal intubation procedure (20.8 ± 6 vs. 22.8 ± 7.3 s; P = 0.33), the number of attempts for successful intubation and oxygen desaturation between groups. Conclusion: Premedication with remifentanil has good analgesic effects for endotracheal intubation in premature infants without significant derangements in mean blood pressure and oxygen saturation.